Adsorbents for Mercury Vapour Recovery in Demercuration Technology - L. M. Levchenko; A. A. Galitsky; V. V. Kosenko; V. N. Mitkin; A. K. Sagidullin; B. M. Shavinsky (Adsorption Science & Technology)
Various adsorbents, including iodides and sulphides of some metals and modified carbon materials, were synthesized and their ability to recover mercury was studied. Our results showed that copper sulphide [dynamic capacity (DC) of 36 mg/g for mercury vapour], the active form of manganese dioxide (DC of 28 mg/g) and modified carbon adsorbents were promising demercuration agents. The DC of the best demercuration agents (MNCS–O–Cl–I) can be as much as 125 mg/g.